„Vigyázzunk a Történetre!” Egyházi helyzetértelmezés néhány személyes és gyakorlati teológiai impulzus alapján - KOCSEV, Miklós (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
“Let Us Safeguard the Story!” An Interpretation of the Church Situation Based on Some Personal and Practical Theological Impulses. Our Reformed Church in Hungary and its everyday life are undergoing changes – similarly to other European churches. We have been experiencing this for a long time, and the direction of change is not very encouraging. This leads to my questions: How did we get into this situation, and how do I interpret this new situation? What challenges does the Christian church face in the context of today’s Hungarian society? In this study, on the one hand, I briefly interpret the processes that affect the life of churches/denominations, especially the Hungarian Reformed Church. On the other hand, I confront the obstacles that we ourselves have created, thereby weakening our own position. Then I look for the opportunities offered by practical theology that can lead to a renewed church life. The path of interpreting the situation and finding a way is (self-)critical, but I believe that it is necessary for the future of the Church. All of this is based on my very personal impressions and search for solutions regarding the Christian church – in this case, primarily in the context of the Reformed Church in Hungary.